2013
DOI: 10.4103/1305-7456.120677
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficiency of photodynamic therapy with different irradiation durations

Abstract: Objective:This study aimed to evaluate the antimicrobial efficiency of PDT and the effect of different irradiation durations on the antimicrobial efficiency of PDT.Materials and Methods:Sixty freshly extracted human teeth with a single root were decoronated and distributed into five groups. The control group received no treatment. Group 1 was treated with a 5% sodium hypochlorite (NaOCl) solution. Groups 2, 3, and 4 were treated with methylene-blue photosensitizer and 660-nm diode laser irradiation for 1, 2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 34 publications
(37 reference statements)
0
27
0
2
Order By: Relevance
“…9 Moreover, the photosensitivity agents used in this research varied, consisting of photosensitisers containing toluidine blue which were derived from Fotosan, a class of phenothiazines that can kill bacteria at low concentrations without causing toxicity in the surrounding tissue. 13 Another potential factor is the use of optical fiber. Fiber in photoactivation can produce a superior effect because it can help to reach difficult-to-access areas.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, the photosensitivity agents used in this research varied, consisting of photosensitisers containing toluidine blue which were derived from Fotosan, a class of phenothiazines that can kill bacteria at low concentrations without causing toxicity in the surrounding tissue. 13 Another potential factor is the use of optical fiber. Fiber in photoactivation can produce a superior effect because it can help to reach difficult-to-access areas.…”
Section: Discussionmentioning
confidence: 99%
“…Yildirim and others compared the eradicative effect of 5% NaOCl for 15 min with PDT for 1 min and found that they were similar. However they analysed planktonic microbes rather than biofilm . A similar result was reported by Xhevdet and others for 2.5% NaOCl irrigation for 5 s and PDT for 1 min against E. faecalis and C. albicans .…”
Section: Discussionmentioning
confidence: 99%
“…Yildirim et al, in evaluation of the effects of different light exposure durations on E. faecalis reduction, concluded that irradiation for 1 minute is adequate to achieve the antimicrobial effect. 42 Moreover, they found that by increasing the irradiation dose the antimicrobial effect was slightly greater, although this difference was not significantly important. In addition, Nunes et al reported comparable insignificant antimicrobial efficiency for different irradiation time in groups using MB and a diode laser for aPDT.…”
Section: Discussionmentioning
confidence: 99%